EVALUASI KETERPAKAIAN KOLEKSI BAHAN PUSTAKA DI UPT PERPUSTAKAAN UNIVERSITAS HALU OLEO - Irmayana Irmayana (Laboratorium Ilmu Komunikasi, Fakultas Ilmu Sosial dan Ilmu Politik (FISIP) Universitas Ha, 2017)
Problems in this research is how the level of kespakaian library collection at UPT Library University Halu Oleo. The purpose of this study to determine the collection of library collection at the University Library Unit Halu Oleo.The method used in this study there are two methods namely the first method is to select the sample book of the total collection in the library, after that check about the use of the collection is recorded by the library. The second method is a method that uses all the populations to be a research sample and uses the help of ten main classes ie the 000-999 class to facilitate sampling. Technique of collecting data using observation and checklist.Population in this research is library collection at UPT Library of Universirtas Halu Oleo with sampling technique of Proportional random sampling 2,466 eksamplar. The scale of confidence is set to 100% with a deviation scale of 0.05. From the analysis of data collection of the largest collection of literature items are in the class 300-399 with 89.4% percentage while the lowest collection of libraries collection is in two classes of 400-499 class with 24.3% percentage and class of 800-899 with 24.3% percentage. Keywords: Evaluation, Evaluation of Dressing, Collection, Library Material, Classification.